Indonesia-South Korea Defense Cooperation In Indonesian Defense Diplomacy: Opportunities And Challenges - Fatrianshar, Hikmah; Purnama, Chandra; Bainus, Arry (Ilomata International Journal of Social Science, 2025)
This research focuses on understanding Indonesia's defense diplomacy efforts in strengthening defense cooperation with South Korea. This research specifically looks at opportunities and challenges in defense cooperation between Indonesia and South Korea using defense diplomacy. This study uses a qualitative method using two types of data: primary data through interviews and secondary data collected from various sources such as electronic publications and electronic media. This study finds that Indonesia has built defense diplomacy that opens up new opportunities for defense cooperation and strives to overcome challenges in defense cooperation between the two countries through various forms of defense diplomacy. This study concludes that Indonesia's defense cooperation with South Korea in Indonesia's defense diplomacy is a strategic step to improve Indonesia's defense capabilities. The implications of the results of this study are to improve the quality and quantity of bilateral contacts between military defense officials and defense diplomacy strategies and show the importance of defense diplomacy in maintaining relations with other countries.